An integrated improvement framework for sharing assessment lessons learned - Rubio, Diego Martín (2008)
Nowadays, an increasing number of companies are using process improvement models as a mean to improve the quality of their processes and therefore the quality of their products and services. Although various improvement frameworks exist that provide organizations with aids in their respective process improvement programs, there is a lack of synergy between organizations using similar frameworks. In this paper we propose an improvement framework that uses the University as an independent collector to integrate the results of improvement efforts and provide analyzed information and resulting artifacts to relevant stakeholders. Since many organizations are currently using multiple models for process improvement, the framework proposed was designed to support multi model information. It also provides an expanded set of data by incorporating the results from all process improvement assessments regardless of the assessment method used. In particular, informal assessments which are usually not included on analyses, proved to be a useful way of obtaining information related to the learning experience that companies undergo in their process improvement journey Initial results of its usage are presented, including the analysis of 40 assessments. Finally, common errors and risk-prone areas are highlighted and the products and services being developed on those key areas are presented (e.g. e-learning material, implementation guidelines, etc)